The Influence of Transformational Leadership, Work–Life Balance, and Organizational Citizenship Behavior on Employee Performance in the East Java Provincial Forestry Office, Jember Branch - Putra, Hafidz Ihza Restu; Setyowati, Trias; Umamy, Septy Holisa; -, Nursaid (Borobudur Management Review, 2025)
The complexity of human resource management in the modern era requires organizations to prepare various supporting elements, ranging from organizational structure to adequate infrastructure. Human resource management at the East Java Provincial Forestry Office, Jember Regional Branch, demonstrates performance dynamics that reflect service quality and organizational effectiveness. This study aims to analyze the influence of transformational leadership style, work-life balance, and organizational citizenship behavior on employee performance. This research involved all employees as samples, totaling 35 employees. The sampling technique used nonprobability sampling with a saturated sampling technique approach. The collected data were analyzed using validity tests, reliability tests, and multiple linear regression. The research results show that transformational leadership style, work-life balance, and organizational citizenship behavior have positive and significant effects on employee performance at the East Java Provincial Forestry Office, Jember Regional Branch, where each variable has potential in improving employee performance. This can serve as a strategic consideration step to enhance employee performance. Recommendations for future research include expanding the study scope and deepening the interaction between factors to enrich adaptive human resource management policies.